Engineering the defect state and reducibility of ceria based nanoparticles for improved anti-oxidation performance. Issue 33 (31st July 2015) - Wang, Yan-Jie; Dong, Hao; Lyu, Guang-Ming; Zhang, Huai-Yuan; Ke, Jun; Kang, Li-Qun; Teng, Jia-Li; Sun, Ling-Dong; Si, Rui; Zhang, Jing; Liu, Yan-Jun; Zhang, Ya-Wen; et al.
Abstract : In this article, we show a robust method to engineer the anti-oxidation performance of CeO2 nanoparticles through the modification of defect state and reducibility. Abstract : Due to their excellent anti-oxidation performance, CeO2 nanoparticles receive wide attention in pharmacological application. Deep understanding of the anti-oxidation mechanism of CeO2 nanoparticles is extremely important to develop potent CeO2 nanomaterials for anti-oxidation application. Here, we report a detailed study on the anti-oxidation process of CeO2 nanoparticles. The valence state and coordination structure of Ce are characterized before and after the addition of H2 O2 to understand the anti-oxidation mechanism of CeO2 nanoparticles. Adsorbed peroxide species are detected during the anti-oxidation process, which are responsible for the red-shifted UV-vis absorption spectra of CeO2 nanoparticles. Furthermore, the coordination number of Ce in the first coordination shell slightly increased after the addition of H2 O2 . On the basis of these experimental results, the reactivity of coordination sites for peroxide species is considered to play a key role in the anti-oxidation performance of CeO2 nanoparticles. Furthermore, we present a robust method to engineer the anti-oxidation performance of CeO2 nanoparticles through the modification of the defect state and reducibility by doping with Gd 3+ . Improved anti-oxidation performance is also observed in cell culture, where the biocompatible CeO2 -based nanoparticles can protect INS-1 cells from oxidative stress induced by H2 O2, suggesting the potential application of CeO2 nanoparticles in the treatment of diabetes.